Emerging Pollutants in the Environment Current and Further Implications - Larramendy, Marcelo L.; Soloneski, Sonia (IntechOpen, 2015)
This edited book, Emerging Pollutants in the Environment Current and Further Implications, includes overviews by significant researchers on the topic of emerging pollutants toxicology, which covers the hazardous effects of common emerging xenobiotics employed in our every day anthropogenic activities. We hope that this book will meet the expectations and needs of all those who are interested in the negative implications of several emerging pollutants on living species.